Increasing The Creativity Of Teenagers In Rendang Village Through The Creation Of The Balaganjur "Jajar Wali" Composition | Meningkatkan Kreativitas Remaja Di Desa Rendang Melalui Penciptaan Komposisi Balaganjur “Jajar Wali” - Bayu Apriana, I Komang (GHURNITA: Jurnal Seni Karawitan, 2024)
Adolescence is a transition period from childhood to adulthood, including mental, emotional, social, and physical maturity. In a cultural context, especially in Bali, teenagers certainly have a vital role because they will carry on the cultural heritage of their predecessors in the area where they live. In Rendang Village, a custom has become part of the culture, namely matetegen. Matetegen is a culture where people from different banjars in Rendang village exchange their living environments with the aim that later, if there are people from one of the banjars holding a Yadnya ceremony, people from other banjars can come together to help with the ceremony. From this culture, the author was inspired to create a work entitled "Jajar Wali," which will focus on teenagers in Rendang Village. In Balaganjur's "Jajar Wali" work, the artist relies on local arts and cultures in Rendang village by pouring them into the medium of Balaganjur Semarandana gamelan to create a harmonious atmosphere and give a majestic impression.